An interview with Professor Ts. Dr. Mohd Nazip Suratman, Deputy Vice-Chancellor (Research and Innovation), Universiti Teknologi MARA - Mohamad Jamil, Norashirene (Faculty of Applied Sciences, 2021)
Professor Ts. Dr. Mohd Nazip Suratman is a Professor of Forestry at the Faculty of Applied Sciences, UiTM Shah Alam, Selangor. His research interests include the use of satellite remote sensing for forest resource management. He holds a Bachelor of Science in Forestry from Universiti Pertanian Malaysia (UPM) and a Master of Science in Forestry from the University of Nebraska-Lincoln (UNL) in the United States of America. In 1998, he was awarded a Canadian Commonwealth Fellowship Program Scholarship to pursue his PhD studies at University of British Columbia (UBC), Vancouver, Canada.